1997
DOI: 10.1074/jbc.272.51.31979
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Human β4-Galactosyltransferases

Abstract: BLAST analysis of expressed sequence tags (ESTs) using the coding sequence of the human UDP-galactose:␤-N-acetylglucosamine ␤1,4-galactosyltransferase, designated ␤4Gal-T1, revealed a large number of ESTs with identical as well as similar sequences. ESTs with sequences similar to that of ␤4Gal-T1 could be grouped into at least two non-identical sequence sets. Analysis of the predicted amino acid sequence of the novel ESTs with ␤4Gal-T1 revealed conservation of short sequence motifs as well as cysteine residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(98 citation statements)
references
References 85 publications
2
96
0
Order By: Relevance
“…␤4Gal-T1 to -T6 exhibit activity to transfer Gal to GlcNAc with a ␤1,4-linkage in N-and O-glycans and glycolipids (1)(2)(3)(4). ␤4Gal-T7 synthesizes the Gal␤1-4Xyl structure that occurs in the linkage portion of glycosaminoglycans (5,6).…”
mentioning
confidence: 99%
“…␤4Gal-T1 to -T6 exhibit activity to transfer Gal to GlcNAc with a ␤1,4-linkage in N-and O-glycans and glycolipids (1)(2)(3)(4). ␤4Gal-T7 synthesizes the Gal␤1-4Xyl structure that occurs in the linkage portion of glycosaminoglycans (5,6).…”
mentioning
confidence: 99%
“…The six ␤4Gal-Ts have highly conserved sequence motifs in the putative catalytic domain including four conserved cysteine residues. The genomic organization of the first four genes is similar and includes conservation of spacing for five intron/exon boundaries in the coding regions (4,7,9,10). This suggests that these genes arose late in evolutionary terms as a result of gene duplication and subsequent sequence divergence.…”
mentioning
confidence: 79%
“…The effects of these substitutions are in agreement with predictions based on x-ray crystallography data on the catalytic unit of ␤4Gal-T1. 4 The region around Ala 186 corresponds to a ␤4Gal-T7, Seventh Member of ␤4-Galactosyltransferase Familysegment in ␤4Gal-T1 that is included in the protein core. The adjacent Pro and His residues at positions 182 and 184 in ␤4Gal-T7 are strictly conserved among all human ␤4GalT sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them are able to synthesize N-acetyllactosamine on glycoproteins. which is potentially further modified by GlcAT-P. We recently reported that ␤4GalT-II-deficient mice showed similar phenotypes to GlcAT-P-deficient mice with a reduction in HNK-1 expression and impaired spatial learning and memory (19), although HNK-1 expression was unaltered in the ␤4GalT-I-deficient mouse brain (20) despite the similarity in primary structure and acceptor specificity of these two enzymes (21,22). These results indicated that ␤4GalT-II has specific roles in the biosynthesis of HNK-1 carbohydrate.…”
mentioning
confidence: 99%